Three cartularies from thirteenth-century Auxerre - Bouchard, Constance Brittain; Medieval Academy of America (Toronto [Ont.] : Published for the Medieval Academy of America by University of Toronto Press, 2012)
"This edition presents the recently rediscovered episcopal cartulary of Auxerre, composed in the 1280s but assumed lost since the French Revolution. [It] also includes the short thirteenth-century cartularies of the nuns of St-Julien and of the cathedral chapter, the latter existing only in fragmentary form."--Publisher description.
Chronological list of Documents -- The Bishop's Cartulary -- The Cathedral Chapter's Cartulary -- The Cartulary of St-Julien.
Includes the Latin text of the cartularies with English annotations and summaries.
Includes bibliographical references (pages 233-235) and indexes.
Keywords: Catholic Church. -- Bishopric of Auxerre (France) -- History -- Sources; Monasticism and religious orders for women -- France -- Auxerre -- History -- Middle Ages, 600-1500 -- Sources; Cartularies; Auxerre (France) -- Church history -- Sources; HISTORY / Medieval; RELIGION / Institutions & Organizations; Electronic books